Assessment of genetic variability in different kenaf (Hibiscus cannabinus) germplasm using morpho-agronomic traits - Arju Miah; Nihar Saha; Md S M Shahriar Parvej; Md. Ali; A K M Shahadat Hossain; Sayma Farabi; Amit Basunia (Innovations in Agriculture, 2020)
Kenaf (Hibiscus cannabinus L.) is a fiber crop classified in the genus Hibiscus (Malvaceae), and has a great potential for its multipurpose utilization, in addition to its traditional usage. Varietal identification of kenaf is always problematic and knowledge on genetic variability of kenaf varieties is also limited, which significantly hindered our effective utilization and conservation of the valuable kenaf germplasm. In order to find a proper method for identifying kenaf varieties and studying their variation, morpho-agronomic characters were analyzed. Fifty eight accessions of kenaf germplasm collected from Gene Bank Department of Bangladesh Jute Research Institute were characterized at Jute Agriculture Experiment Station, Manikganj during April 2014 to December 2014. The accessions were characterized for fifteen morpho-agronomic attributes as per Hibiscus descriptor in order to select superior genotypes for the genetic improvement of kenaf. Considerable ranges of variability were observed in stem colour, petiole colour, plant height, base diameter, dry fibre weight, dry core weight, green weight with leaves and green weight without leaves. Based on major yield contributing characters accessions 1653, 3384, 3928 and 4202 performed better than the control varieties HC-2 and HC-95.